2021
DOI: 10.1097/md.0000000000026623
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of Cyclin F in liver cancer predicts poor prognosis

Abstract: Background:Cyclin F (CCNF) dysfunction has been implicated in various forms of cancer, offering a new avenue for understanding the pathogenic mechanisms underlying hepatocellular carcinoma (HCC). We aimed to evaluate the role of CCNF in HCC using publicly available data from The Cancer Genome Atlas (TCGA).Method:We used TCGA data and Gene Expression Omnibus (GEO) data to analyze the differential expression of CCNF between tumor and adjacent tissues and the relationship between CCNF and clinical characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…These two reports suggest that CCNF is likely to be a tumor suppressor gene. However, studies have also shown that the overexpression of CCNF predicts a poor prognosis in ovarian cancer ( 14 ), liver cancer ( 15 ) and skin melanoma ( 16 ), suggesting that CCNF is an oncogene. Although contradictory, the above reports revealed that the functions of CCNF are likely to be related to the state of cells ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…These two reports suggest that CCNF is likely to be a tumor suppressor gene. However, studies have also shown that the overexpression of CCNF predicts a poor prognosis in ovarian cancer ( 14 ), liver cancer ( 15 ) and skin melanoma ( 16 ), suggesting that CCNF is an oncogene. Although contradictory, the above reports revealed that the functions of CCNF are likely to be related to the state of cells ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that altered CCNF expression is associated with a poor prognosis in various cancers, including breast, liver, pancreatic, brain, and skin cancers 12 14 , 37 . In the current study, the analysis of the data from the TCGA database reveals that 45.89% of ccRCC patients are characterized by high CCNF mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Another example is liver cancer, where an elevated level of CCNF was associated with worse OS. Additionally, this overexpression cannot be led by the mutations in the CCNF gene because only 0.81% of 372 liver cancer patients bear the mutation in CCNF locus 14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations